Depositional controls on lacustrine coquinas from an early cretaceous rift lake: Morro do Chaves Formation, Northeast Brazil. (February 2021) - Favoreto, Julia; Valle, Bruno; Borghi, Leonardo; Dal' Bó, Patrick Führ; Mendes, Marcelo; Arena, Michele; Santos, Jeferson; Santos, Hélisson; Ribeiro, Carolina; Coelho, Pedro
Abstract: The Morro do Chaves Formation is a hybrid sedimentary succession composed of shell beds interbedded with mudstones and sandstones deposited during the rifting process of the Gondwana in a complex lake rift system, forming one of the thickest coquina deposits around the world. Despite being deeply investigated over the last decades in outcrops, the entire stratigraphic organization is not well understood yet, mainly because of the absence of continuous well core data, in addition to challenging geometries and facies distribution of the shell beds. This study focus on the characterization of facies and facies associations, and the development of a conceptual depositional model for the Morro do Chaves Formation, based on the analysis of four continuous well cores and the stratigraphic correlation among them. The described carbonate and carbonate-hybrid rocks are composed mainly of bivalves that form flat shell banks developed during dry periods with low tectonic activity. The siliciclastic rocks (mudstones, sandstones and hybrid rocks) occur interbedded with the carbonate rocks and indicates periods of active tectonic and/or climatic wet periods. The deposits are arranged in a hierarchical organization of 6 m-scale T-R cycles showing aggradation and progradation patterns. The system is controlled mainly by allocyclic (e.g., tectonics and climate) and the autocyclic (e.g., waves and currents) processes. The maximum regressive surface record an important change in the environment with a gradual increase of terrigenous input into the basin until the fast creation of accommodation space for the deposit of extensive shales that drowned and mark the end of the shell bank system. This study on facies, geometries and stratigraphic surfaces adds new and useful knowledge for helping in the understanding of complex coquina reservoirs and is applicable in the exploration of new areas with correlate lacustrine systems. Highlights: Depositional model of shell accumulation is proposed based on a new relevant stratigraphic and sedimentologic dataset. Shallow and subaqueous bivalve spit was recognized in a lacustrine environment influenced by longshore currents. The maximum lake contraction is marked by palustrine facies and mudcracks. The expansion phase lake is marked by a tectonic limit which drowned the shell banks. Autocyclic controls of the environment are reflected in shell fragmentation degree.